2009
DOI: 10.1371/journal.pone.0007817
|View full text |Cite
|
Sign up to set email alerts
|

The ASH1 HOMOLOG 2 (ASHH2) Histone H3 Methyltransferase Is Required for Ovule and Anther Development in Arabidopsis

Abstract: BackgroundSET-domain proteins are histone lysine (K) methyltransferases (HMTase) implicated in defining transcriptionally permissive or repressive chromatin. The Arabidopsis ASH1 HOMOLOG 2 (ASHH2) protein (also called SDG8, EFS and CCR1) has been suggested to methylate H3K4 and/or H3K36 and is similar to Drosophila ASH1, a positive maintainer of gene expression, and yeast Set2, a H3K36 HMTase. Mutation of the ASHH2 gene has pleiotropic developmental effects. Here we focus on the role of ASHH2 in plant reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 56 publications
4
108
0
2
Order By: Relevance
“…sdg2 mutant flowers contain normal numbers of floral organs and a relatively normal morphology, except that the stamens remain short during later flower developmental stages (stage definition according to Smyth et al, 1990; Figure 1C). Homeotic conversion of floral organs, as had been previously reported for the atx1-1 (Alvarez-Venegas et al, 2003) and sdg8-1/ashh2-1 (Grini et al, 2009) mutants, was not observed in sdg2 mutants. In sdg2 mutants, the short stamens failed to reach the receptive stigmatic papillae of the pistil at anthesis for successful pollination.…”
Section: Loss Of Function Of Sdg2 Results In Smaller Plantssupporting
confidence: 77%
See 2 more Smart Citations
“…sdg2 mutant flowers contain normal numbers of floral organs and a relatively normal morphology, except that the stamens remain short during later flower developmental stages (stage definition according to Smyth et al, 1990; Figure 1C). Homeotic conversion of floral organs, as had been previously reported for the atx1-1 (Alvarez-Venegas et al, 2003) and sdg8-1/ashh2-1 (Grini et al, 2009) mutants, was not observed in sdg2 mutants. In sdg2 mutants, the short stamens failed to reach the receptive stigmatic papillae of the pistil at anthesis for successful pollination.…”
Section: Loss Of Function Of Sdg2 Results In Smaller Plantssupporting
confidence: 77%
“…By contrast, downregulation of AG, PI, AP2, and AP1 was shown in atx1-1, with flowers exhibiting homeotic conversions and variable aberrations (Alvarez-Venegas et al, 2003). sdg8-1/ashh2-1 has also been reported to display downregulation of PI, AP2, and AP1, with a low proportion of flowers exhibiting homeotic conversions (Grini et al, 2009). Furthermore, the sdg2 mutants differ in the flowering time phenotype from previously studied TrxG family gene mutants.…”
Section: Sdg2 In Regulation Of Sporophyte Developmentmentioning
confidence: 69%
See 1 more Smart Citation
“…The sdg8 mutant shows several pleiotropic phenotypes, such as early flowering, altered shoot and root architecture, altered pathogen resistance, male sterility, abnormal sporophyte and gametophyte development (Kim et al 2005;Cazzonelli et al 2009a;Grini et al 2009;Berr et al 2010). A few putative target genes responsible for these phenotypes have been described and target gene loci show a lower abundance of H3K4 or H3K36 methylation marks, as well as reduced mRNA levels in the sdg8 mutant.…”
Section: Epigenetic Maintenance Of Carotenoid Compositionmentioning
confidence: 99%
“…H3 Lys-36 trimethylation (H3K36me3) is a highly conserved histone mark and is primarily correlated with active gene expression in eukaryotes (Roudier et al, 2011;Wen et al, 2014). In Arabidopsis (Arabidopsis thaliana), H3K36me3 is enriched at the gene-body regions and plays an important role in regulating the expression of development-related genes involved in brassinosteroid signaling pathways, carbon and light responses, floral organ development, and flowering (Xu et al, 2008;Grini et al, 2009;He et al, 2011;Wang et al, 2014;Yang et al, 2014;Li et al, 2015). Deposition of H3K36 methylation is mediated by a collection of conserved SET domain-containing group (SDG) histone methyltransferases.…”
mentioning
confidence: 99%